Androgens and male sexual function. Issue 4 (July 2022) - Corona, Giovanni; Rastrelli, Giulia; Vignozzi, Linda; Maggi, Mario
Abstract : Sexual symptoms are the most specific determinants of low testosterone (T) observed during adulthood. In this narrative review, we summarize the most important evidence supporting the positive relationships between endogenous T levels and sexual activity in the adult male, by using preclinical and clinical observations. In addition, we also report an update of our previous meta-analysis evaluating the effects of T treatment (TRT) on sexual functioning in subjects with T deficiency. Available data indicate that TRT of symptomatic hypogonadal men can improve several aspects of sexual life, including erection. However, the effect is rather modest and lower in subjects with associated metabolic conditions. The specific observed effects are similar to those derived from lifestyle intervention. Since TRT might result in body composition improvement, it is reasonable to suppose that an initial treatment with T can improve the willingness of hypogonadal subjects to perform physical exercise and to adhere to a healthier behavior. Similar data were derived from animal models. However, it should be important to recognize that lifestyle modifications should be the first step to promote weigh reduction. TRT can be combined with lifestyle interventions only in symptomatic hypogonadal subjects especially in the presence of comorbid metabolic conditions.